ANALISIS KINERJA KEUANGAN SEBELUM DAN SAAT PANDEMI COVID-19 (STUDI KASUS BUNDA LAUNDRY) - Wahyuni, Indah Dwi; Giyartiningrum, Eko (Journal Competency of Business, 2022)
This study aims to determine the financial performance of Bunda Laundry before and during the Covid-19. This research is a quantitative research using observation and interview methods as data collection. Financial performance in this study was measured using Current Ratio, Cash Ratio, Debt to Equity Ratio, ROI, and Total Asset Turn Over. The results of this study show that there are differences in the financial performance of Bunda Laundry before and during the Covid-19 pandemic when viewed from the Current Ratio, Cash Ratio, Debt to Equity Ratio, ROI, and Total Asset Turn Over.